Seismic performance of structures composed of T-shaped and L-shaped recycled concrete columns and lightweight infill walls - Cun Hui; Yongbo Zhang; Pan Liu; Ran Hai (Journal of Asian Architecture and Building Engineering, 2020)
In this paper, a structure composed of a T- or L-shaped recycled concrete column frame (RCCF) and lightweight infill wall (LIW) with a herringbone brace has been proposed to investigate its seismic behavior. Two T-shaped and two L-shaped full-size experimental models of the structure have been built and tested under low-cyclic loading conditions. Consequently, bearing capacity, stiffness, ductility, hysteretic behavior, energy dissipation, and failure characteristics of each test specimen have been analyzed, identifying structure parts prone to damage and failure, understanding their yield mechanisms, and lastly providing constructive recommendations for the structural design. Studies show that the bearing capacity, ductility, and comprehensive seismic behavior of T- or L-shaped lattice-reinforced RCCF-LIW structures with a herringbone brace have been significantly improved. For the engineering practice, it is necessary to strengthen the performance of the herringbone brace-frame beam joint.